2006
DOI: 10.1063/1.2356857
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel bioreactor to apply shear stress and tensile strain simultaneously to cell monolayers

Abstract: To date many bioreactor experiments have investigated the cellular response to isolated in vitro forces. However, in vivo, wall shear stress ͑WSS͒ and tensile hoop strain ͑THS͒ coexist. This article describes the techniques used to build and validate a novel vascular tissue bioreactor, which is capable of applying simultaneous wall shear stress and tensile stretch to multiple cellular substrates. The bioreactor design presented here combines a cone and plate rheometer with flexible substrates. Using such a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…This validation approach also considered the shallow indents on the plate surface. These shallow indents did affect the flow at the localized edge regions of the shallow indent, but his effect was minimal and had an insignificant effect on the over WSS applied to the cellular samples (see Breen et al 9 for further details).…”
Section: Computational Fluid Dynamic Calibration and Validation For Umentioning
confidence: 95%
See 2 more Smart Citations
“…This validation approach also considered the shallow indents on the plate surface. These shallow indents did affect the flow at the localized edge regions of the shallow indent, but his effect was minimal and had an insignificant effect on the over WSS applied to the cellular samples (see Breen et al 9 for further details).…”
Section: Computational Fluid Dynamic Calibration and Validation For Umentioning
confidence: 95%
“…However, in the experimental study reported here, involving unsteady flow, varying WSS waveforms were desired, each requiring a corresponding CAV profile. The linear relationship determined in Breen et al 9 for steady flow (and the resulting master curve) were insufficient to directly determine the appropriate CAV profiles due to the unsteady nature of the flow and the inertia and momentum effects associated with mimicking physiological (mechanical) stimuli. In order to account for momentum/inertia effects, the CFD preprocessor flow state within Ansys-CFX was set to ''transient flow.''…”
Section: Computational Fluid Dynamic Calibration and Validation For Umentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the amount of shear stress on the cells through the perturbation of the media was unable to be measured. Other bioreactors include the compression of a media-filled substrate with loadinduced flow (Tanaka et al, 2005) and a cone-and-plate viscometer with additional tension (Breen et al, 2006). Although these bioreactors, in some way, apply two different types of loading, they are not designed to examine the effects of these loading modes individually or to quantify these loads explicitly.…”
Section: Discussionmentioning
confidence: 98%
“…Research in cell chemotaxis can be easily performed while further integrating a microfluidic gradient generator [22]. In mechanical stress stimulation experiments, a conventional bioreactor uses a compressive loading cylinder [23], rotating cone [24,25], or parallel plate chamber [26] to generate hydrostatic pressure or shear stress on cells. With a microfluidic device, on the other hand, physical shear stress can be simply created by fluid flow induction from laminar microflow behavior [27], and hydrostatic pressure can be created by a vortex in the PDMS chamber [28].…”
Section: Introductionmentioning
confidence: 99%